Clever inventors - Nicholson, Sue; Remonetti, Flavio (Essex Miles Kelly Publishing Ltd, 2023)
This book is full of amazing answers! Humorous illustrations and extraordinary facts explore ingenious, imaginative and incredible inventions from clever inventors young and old
Famous People
Keywords: inventors